Research on the function hazard assessment of continuously varying systems based on fuzzy sets - SUN Kuan; ZHANG Shuguang; WANG Zhu (Hangkong gongcheng jinzhan)
When assessing function hazard on time and function continuously varying systems, it is often difficult for the assessor to evaluate the effect of the function performance. The method based on SAE ARP 4761 does not provide an assessable way to evaluate continuous systems, but only addresses a limited number of failure modes.Therefore, the assessable function failure data are combined with fuzzy set to establish membership functions. By introducing function performance and time into two-dimensional normal distribution function and its variants, the function hazard can be divided into different levels. Taking the impact of UAV motor as an example, the function hazard assessments based on fuzzy set and experience are applied for a comparison. The results show that by calibrating the condition of the motor system and conducting fuzzy set FHA evaluation, a quantitative evaluation effect can be obtained, which is suitable for the required evaluation task.